2018
DOI: 10.1371/journal.ppat.1006867
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus UL23 inhibits transcription of interferon-γ stimulated genes and blocks antiviral interferon-γ responses by interacting with human N-myc interactor protein

Abstract: Interferon-γ (IFN-γ) represents one of the most important innate immunity responses in a host to combat infections of many human viruses including human herpesviruses. Human N-myc interactor (Nmi) protein, which has been shown to interact with signal transducer and activator of transcription (STAT) proteins including STAT1, is important for the activation of IFN-γ induced STAT1-dependent transcription of many genes responsible for IFN-γ immune responses. However, no proteins encoded by herpesviruses have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 64 publications
2
57
0
2
Order By: Relevance
“…The observations that ΔM32 grew in NIH3T3 cells indicate that M32 is not required for MCMV replication in vitro . Thus, in contrast to its HCMV homolog pUL32, which is essential for HCMV replication (29, 31), M32 is not essential—though important—for MCMV replication in vitro .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The observations that ΔM32 grew in NIH3T3 cells indicate that M32 is not required for MCMV replication in vitro . Thus, in contrast to its HCMV homolog pUL32, which is essential for HCMV replication (29, 31), M32 is not essential—though important—for MCMV replication in vitro .…”
Section: Resultsmentioning
confidence: 95%
“…To generate ΔM32, we adopted our previously-published protocols for generating gene-deletion mutants of HCMV to mutagenize a BAC clone of the wild-type MCMV (Smith strain) genome (MCMV BAC ) by deleting the M32 open reading frame (28-30). Furthermore, rescued viral mutant, R-M32, was generated from ΔM32, by restoring the M32 sequence, following the procedures as described previously (29, 31). Deletion of the M32 gene in ΔM32 and the restoration of the M32 sequence in R-M32 were confirmed by PCR and Southern blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many viruses are not sensitive to the IFN response or produce factors that interfere with IFN and interferon‐stimulated genes (ISGs) . As IFN levels in uninfected individuals are typically vanishingly low, the high persistent presence of IFNs and/or their induced genes (ISGs) may also complicate or even cause other diseases, such as lupus or atopic dermatitis.…”
Section: Finding New Uses For Approved Drugsmentioning
confidence: 99%
“…UL23, the viral gene targeted by our drive, was initially thought to be dispensable for hCMV replication in fibroblasts (13,18). Serendipitously, it was later showed that UL23 is a tegument protein that blocks antiviral interferon-γ (IFN-γ) responses by interacting with human N-myc interactor (Nmi) protein (19). As a result, the growth of UL23-knockout viruses is severely inhibited in infected cells treated with IFN-γ.…”
Section: Main Textmentioning
confidence: 99%